ANALISIS RANTAI PASOK PRODUK PERIKANAN TANGKAP BAGAN APUNG DI TATELI WERU (BULOH) KECAMATAN MANDOLANG KABUPATEN MINAHASA - Wahiu, Rally Y.; Andaki, Jardie A.; Wasak, Martha P. (AKULTURASI: Jurnal Ilmiah Agrobisnis Perikanan, 2019)
AbstractSupply chain is a network of independent and interconnected organizations that work together cooperatively and mutually beneficial in controlling, managing and improving the flow of material and information from suppliers to consumen.Fisheries are all the activities related to management and utilization of fish resources and the environment starting from pre-production, production, processing to marketing, which are carried out in a fisheries business system. Fishing is an activity to obtain fish in waters that are not in a state cultivated by any ways , including the activities that used boat to load, transport, cool, handle, process, or preserve fishes.The types of lift net fishering  in Indonesia, There are 1.bamboo platform lift net 2. Boat lift nets  3. Raft lift nets or Floating lift nets. The types of lift nets at the study of location  is the Raft Chart or Floating lift net.The purpose of this research are to Analyze the supply chain as a result of the fishery lift net in Tateli Weru (Buloh) Mandolang District of Minahasa District and 2.To Find out who are involved in the fishing chain as a result of the fishery catchment in Tateli Weru (Buloh) Mandolang District Minahasa district.The results and discussion of this research that the Supply chain product fishermen in Tateli Weru (Buloh) Mandolang District, Minahasa Regency are 1. Fishermen who have floating lift net 2. Animal Feed Factory, 3. Small traders or petibo, 4. Fishing vessels, 5. Consumen.The mechanism of product is about the  financial and information resources in  supply chain of floating fisheries products at Tateli Weru (Buloh), there are : 1. Channel I: lift net floating fishermen - animal feed mills - consumen I, 2. Channel II: lift net Floating fishermen ,Fishing Vessels and 3. Channels III: lift net Floating fishermen - small traders or petibos - Consumers II. The cyclus of Product  from upstream to downstream, and the financial from downstream to upstream and information  flows in two ways.Keywords: Supply chain, lift net, Floating Bag Fishermen, Product Flow, Financial Flow, Information Flow. AbstrakRantai pasok adalah suatu jaringan dari organisasi-organisasi independen dan saling terhubung yang bekerjasama secara kooperatif dan saling menguntungkan dalam mengontrol, mengatur dan memperbaiki aliran material dan informasi dari pemasok sampai pemakai.Perikanan adalah semua kegiatan yang berhubungan dengan pengelolaan dan pemanfaatan sumberdaya ikan dan lingkungannya mulai dari praproduksi, produksi, pengolahan sampai dengan pemasaran, yang dilaksanakan dalam suatu sistem bisnis perikanan. Penangkapan ikan adalah kegiatan untuk memperoleh ikan diperairan yang tidak dalam keaadaan dibudidayakan dengan alat atau cara apapun, termasuk kegiatan yang menggunakan kapal untuk memuat, mengangkut, menyimpan, mendinginkan, menangani, mengolah, dan/atau mengawetkannyaJenis alat tangkap bagan di indonesia yaitu;1. Bagan Tancap, 2. Bagan Perahu dan 3. Bagan Rakit atau Bagan Apung. Jenis Bagan di lokasi penelitian yaitu Bagan Rakit atau Bagan Apung.Tujuan dari penelitian ini adalah: 1. Menganalisis rantai pasok hasil tangkapan nelayan bagan apungdi Tateli Weru (Buloh) Kecamatan Mandolang Kabupaten Minahasa dan 2. Mengetahui siapa saja yang terlibat dalam rantai pasok hasil tangkapan nelayan bagan apungdi Tateli Weru (Buloh) Kecamatan Mandolang Kabupaten Minahasa.Hasil dan pembahasan dari penelitian ini yaitu: Pelaku rantai pasok produk perikanan tangkap di Tateli Weru (Buloh) Kecamatan Mandolang Kabupaten Minahasa adalah 1. Nelayan pemilik bagan apung, 2. Pabrik Pakan Ternak, 3. Pedagang kecil atau petibo, 4. Kapal pancing, 5. Konsumen.Mekanisme aliran produk, aliran keuangan dan aliran informasi pada rantai pasok produk perikanan tangkap bagan apung di Tateli Weru (Buloh) yaitu: 1. Saluran I: Nelayan bagan apung – pabrik pakan ternak – konsumen I, 2. Saluran II: Nelayan bagan apung – Kapal Pancing dan 3. Saluran III: Nelayan bagan apung – pedagang kecil atau petibo – Konsumen II. Aliran produk mengalir dari hulu ke hilir, aliran keuangan mengalir dari hilir ke hulu dan aliran informasi mengalir dua arah.Kata kunci : Rantai pasok, Jaring angkat, Nelayan Bagan Apung, Aliran produk, Aliran Keuangan, Aliran Informasi